2012
DOI: 10.1016/j.jsb.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human spastin AAA domain

Abstract: Hereditary spastic paraplegia (HSP) is a motor neuron disease caused by a progressive degeneration of the motor axons of the corticospinal tract. Point mutations or exon deletions in the microtubule-severing ATPase, spastin, are responsible for approximately 40% of cases of autosomal dominant HSP. Here, we report the 3.3 Å X-ray crystal structure of a hydrolysis- deficient mutant (E442Q) of the human spastin protein AAA domain. This structure is analyzed in the context of the existing Drosophila melanogaster s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 24 publications
3
33
1
Order By: Relevance
“…To gain further insight into spastin oligomerization, we determined the crystal structure of human spastin in the apo state (Table ). Similar to the result of a previous structural study of human spastin , only the AAA domain was visible in the electron density, while the MTBD region was not visible. However, in the spastin AAA domain structure we determined, the loop linking helix α5 and β4 in the large subdomain and the short helix α9a between helices α9 and α10 in the small subdomain are better structured (Fig.…”
Section: Resultssupporting
confidence: 86%
“…To gain further insight into spastin oligomerization, we determined the crystal structure of human spastin in the apo state (Table ). Similar to the result of a previous structural study of human spastin , only the AAA domain was visible in the electron density, while the MTBD region was not visible. However, in the spastin AAA domain structure we determined, the loop linking helix α5 and β4 in the large subdomain and the short helix α9a between helices α9 and α10 in the small subdomain are better structured (Fig.…”
Section: Resultssupporting
confidence: 86%
“…In this study, the microtubules were severed into small fragments by spastin and spastin ΔN1 . This finding indicated that the function of spastin was closely related to the MTBD domain and AAA domain, which was consistent with the finding of a previous report (Taylor et al ., ). Among the AAA protein family members, spastin can bind to the microtubule via the MTBD domain and disrupt the fence‐like structure of microtubules by AAA ATPase.…”
Section: Discussionmentioning
confidence: 97%
“…Crystal structures of human, yeast and archaeal Vps4 24; 104; 105; 106; 107 , human and D. melanogaster Spastin 108; 109 , and C. elegans Fidgetin-like protein 1 (FIGL-1) 110 , have revealed details of the domain structure (Figure 4). The large AAA ATPase domain contains 5 α-helices that are arranged on either side of a central 5-stranded parallel β-sheet.…”
Section: Aaa Atpase Cassettementioning
confidence: 99%
“…Crystal structures of (a) human VPS4B (PDB ID: 1XWI) 24 , (b) human spastin (PDB ID: 3VFD) 109 and (c) human fidgetin-like 1 (FIGL-1, PDB ID: 3D8B) 110 . Coloring is as in Figure 1.…”
Section: Figurementioning
confidence: 99%